Computation of power indices in the UNPA electoral system - Aguirre, Jesús Francisco (2002)
In this paper we present a computational implementation of the Shapley Value and Banzhaf—Coleman Index of Power. Both indices describe the real power of the coalitions involved in strategic interactions. The system allows to introduce restrictions (incompatibilities) amongsome coalitions. The system also allows the study of complex Electoral Applications. We describe the client—server design and the implementation of these tools, using the languages C and Tcl/Tk. The server program is written in C and requires Linux. The Client Program is written in Tcl/Tk with namespace mechanism and it supports Linux and Windows. Westudy the Electoral Power distribution in the election of authorities in Universidad Nacional de la Patagonia Austral (UNPA). We focus both on the Academic Units Councils and also the Assembly which elect the Deans and Rector respectively.